SENSORLESS FLUX REGION MODIFICATION OF DTC CONTROLLED IM FOR TORQUE RIPPLE REDUCTION - User, Yavuz; Gulez, Kayhan; Ozen, Sukru (ISTANBUL UNIV, FAC ENGINEERING, 2014)
A Direct Torque Control (DTC) drive allows direct and independent control of flux linkage and electromagnetic torque by the selection of optimum inverter switching tables. There is no need for any complex transformation of current or voltage. However, each vector selected from the switching table cannot produce the required accurate stator voltage vector to provide the desired torque and flux. This results in the production of ripples in the torque as well as flux waveforms. In this study, we propose a method to reduce torque and flux fluctuations. In this method, the flux region of conventional DTC model are modificated and is compared to conventional DTC method. Speed is estimated from MRAS. The conventional MRAS-based sensorless DTC and the flux region modification method are simulated and the comparison of their practice performances is presented.
Keywords: Induction motor; Direct torque control; Flux Region modification method; MRAS; Torque and Flux Linkage ripple; Engineering